Nature and national identity after communism : globalizing the ethnoscape - Schwartz, Katrina Z. S. (Pittsburgh, Pa. : University of Pittsburgh Press, 2006)
Examines the intersection of environmental politics, globalization, and national identity in Latvia. Based on ethnographic research and discourse analysis, this book explores that country's post-Soviet responses to European assistance and political pressure in nature management, biodiversity conservation, and rural development.
Introduction -- By land or by sea -- "The occupation of beauty" -- Globalizing the ethnoscape -- Returning to a postproductivist Europe -- "Masters in our native place" : the politics of national parks -- Wild horses in a "European wilderness" -- "Lichens are not our national treasure" : the battle over sustainable forestry -- Conclusion.
Includes bibliographical references (pages 259-275) and index.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
JSTOR
Keywords: Human ecology -- Political aspects -- Latvia; Political ecology -- Latvia; Landscape ecology -- Latvia; Environmental policy -- Latvia; Environmental protection -- Latvia; Conservation of natural resources -- Latvia; Rural development -- Latvia; Latvia -- Environmental conditions; Latvia -- Politics and government; Écologie humaine -- Aspect politique -- Lettonie; Écologie politique -- Lettonie; Écologie du paysage -- Lettonie; Environnement -- Politique gouvernementale -- Lettonie; Environnement -- Protection -- Lettonie; Conservation des ressources naturelles -- Lettonie; Développement rural -- Lettonie; Lettonie -- Politique et gouvernement; Conservation of natural resources; Ecology; Environmental policy; Environmental protection; Human ecology -- Political aspects; Landscape ecology; Political ecology; Politics and government; Rural development; Latvia; Umweltpolitik; Umweltschutz; Developpement rural -- Lettonie; Environnement -- Protection -- Lettonie; Écologie du paysage -- Lettonie; Écologisme -- Lettonie; Postcommunisme -- Lettonie; Écologie humaine -- Aspect politique -- Lettonie; Conservation des ressources naturelles -- Lettonie; Politique de l'environnement -- Lettonie; Lettonie -- Politique et gouvernement -- 1991- ...; Lettland; Geschichte 1989-.